Facility Layout Design of Mr. Budi's Tofu Factory Using the HIRARC Method and Blocplan Algorithm - Tanjung, Rindi Aini; Umam, Muhammad Isnaini Hadiyul; Nur, Muhammad; Suherman, Suherman; Taslim, Rika (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Occupational health and safety is something that cannot be separated in human resources where occupational health and safety includes preventing accidents due to work, securing materials, carrying out maintenance to improve living standards and increase productivity. At the Mr. Budi tofu factory, employees have not used Personal Protective Equipment in the production process and the unstructured layout causes work accidents on the production floor. This study aims to conduct an OHS assessment at the Pak Budi tofu factory and redesign the facility layout to reduce work accidents so that the production process is more effective and efficient. The methods used in this research are HIRARC and Blocplan Algorithm. The results of the OHS assessment at the Pak Budi tofu factory show 2 activities with a medium risk level and one activity with a low risk level, in the redesign of the facility layout the distance of material movement in the initial layout is 19.2 m and the distance of material movement in the proposed layout is 11.7 meters where there is a difference in the distance of material movement of 7.5 meters, this shows that the proposed layout can be applied to the Pak Budi tofu factory.